PENGARUH SERVICE PERFORMANCE DAN CUSTOMER VALUE TERHADAP REPURCHASE DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING (Studi Pada Pengguna Jasa PT Herona Express Semarang) - Antika, Heppy Widya; Farida, Naili; Listyorini, Sari (Jurnal Ilmu Administrasi Bisnis, 2015)
This research is motivated by the fluctuations of the Kiriman Hantaran Berangat (KHB) and not achieving the target turnover predetermined PT Herona Express Semarang in recent years . In addition , the performance of services decreased followed by a decrease in customer ratings. The purpose of this research is conducted to determine the influence of service performance and customer value to repurchase with the customer satisfaction as an intervening variable. Type of research used in this research is explanatory research. The population is a freight forwarder users through PT Herona Express Semarang. The sample are 100 person who have done the repurchase services at least twice, with sample technique used was purposive sampling.The method of analysis used in this study is using a two-stage regression analysis with SPSS for windows 16.0, which previously tested the validity and reliability first. Based on calculations show that variable service performance have an influence to customer satisfaction with the coefficient 0,367. Variable customer value have an influence to customer satisfaction with the coefficient 0,254. Variable customer satisfaction have an influence to repurchase with the coefficient 0,622. The result shows that service performance and customer value has a positive and significant effect (partial)to the customer satisfaction of each 30,5% and 27,2%. Customer satisfaction also has a positive and significant effect (partial)to the repurchase of 38,6%.